Endovascular surgery for thoracic aortic pathologies involving the aortic arch - Lu, Heng; Huang, Ling-chen; Chen, Liang-wan (Frontiers in Cardiovascular Medicine, 2022)
Background Aortic arch pathologies are serious clinical conditions associated with a very dismal prognosis. Traditional open surgery has a high mortality and is not suitable for critically ill patients. Recently years, endovascular treatment of thoracic aorta has made rapid progress and has been gradually applied to the treatment of aortic arch pathologies. However, maintaining cerebral blood flow during endovascular treatment of aortic arch lesions remains a challenge at this time. This study aims to evaluate the feasibility, efficacy, and safety of endovascular treatment of thoracic aortic pathologies involving the aortic arch, and to present initial experience with this technique. Methods From October 2016 to December 2020, patients who met the inclusion criteria were enrolled. All patients underwent thoracic endovascular aortic repair with the proximal landing zone of the stent-graft in the aortic arch at Ishimaru zones 0–1, in which cerebral flow needs to be maintained during surgery, and the supra-aortic branches were reconstruction with either in situ fenestration or the chimney technique. Results A total of 62 cases with lesions involving the arch were treated with endovascular surgery. Total supra-aortic branches reconstruction was successfully performed in 51 cases, the left carotid artery (LCA) and the innominate artery reconstruction were performed in eight cases, the left subclavian artery (LSA) and the LCA were reconstructed in three patients. Among them, the in situ fenestration or chimney repair technique for the LSA was successful performed in 42 and 12 cases. However, in 20 patients, attempts to reconstruction the LSA using the fenestration technique were unsuccessful due to tortuous and angulated vessels. Early mortality was 6.45%. No neurological complications related to surgery occurred. Computer tomography images at post-operative follow-up (mean 3.51 months) confirmed patency of all branch stents without any signs of endoleaks, migration, conversion to retrograde dissection or receive open-heart surgery. Conclusion The endovascular technique is an effective, feasible, safe and repeatable method to reconstruct the aortic arch, which allows for the reconstruction of the supra-aortic branches.